Price Stability and Inflation Persistence During the International Gold Standard: The Scandinavian Case - Ola Honningdal Grytten; Arngrim Hunnes (Norges Bank, 2009)
In the 1870s the three Scandinavian countries Denmark, Norway and Sweden formed the Scandinavian Currency Union. Both the adoption of gold and the monetary union were supposed to lead to price stability in and between these countries. By drawing on new indices of consumer prices the present paper offers an examination of inflation dynamics, defined as price stability and inflation persistence, in the periphery of Scandinavia during the heyday of the international gold standard.
hdl:11250/2497621
Keywords: E31; E42; N13; 330; Scandinavia; currency union; gold standard; inflation persistence; price stability